SEISMIC AND WIND PERFORMANCE OF OUTRIGGER AND BELT TRUSS SYSTEMS IN A 50-STOREY HIGH-RISE BUILDING: A PARAMETRIC STUDY UNDER VARYING SOIL CONDITIONS - Gajendra; Kedar Giri; Sourabh Koralli; Channappa (International Educational Journal of Science and Engineering, 2026)
This study presents a comprehensive parametric investigation on the effectiveness of various lateral load resisting systems for a 50-storey reinforced concrete high-rise building located in Bhuj, classified under Seismic Zone V according to Bureau of Indian Standards IS 1893 (Part 1): 2016. A total of 33 structural configurations were developed and analyzed using ETABS, including single and double outrigger systems, single and double belt truss systems, and hybrid configurations combining outriggers with belt trusses positioned at different floor levels. Dynamic analysis was performed using the Response Spectrum Method (RSA), while wind effects were evaluated in accordance with IS 875 (Part 3): 2015. Structural performance was assessed based on maximum story displacement, inter-storey drift, and base shear response under both seismic and wind loading conditions. Subsequently, the optimum configuration from each structural category was further examined under three different soil conditions, namely Type I (Hard Soil), Type II (Medium Soil), and Type III (Soft Soil), to evaluate soil–structure interaction effects on overall building response. The analytical results indicate that the double combined outrigger with belt truss system positioned at the 10th and 20th storeys demonstrates superior structural efficiency among all models considered. This configuration achieved a reduction of 30.8% in seismic displacement, 27.6% in wind displacement, and 25.3% in story drift, while producing only a marginal increase of 0.3% in base shear. The findings confirm the significant potential of combined outrigger–belt truss systems in enhancing the stability and serviceability performance of tall buildings in high seismic regions.